Altered DNA methylation of glucose transporter 1 and glucose transporter 4 in patients with major depressive disorder. (May 2016) - Kahl, Kai G.; Georgi, Karsten; Bleich, Stefan; Muschler, Marc; Hillemacher, Thomas; Hilfiker-Kleinert, Denise; Schweiger, Ulrich; Ding, Xiaoqi; Kotsiari, Alexandra; Frieling, Helge
Abstract: Alterations in brain glucose metabolism and in peripheral glucose metabolism have frequently been observed in major depressive disorder (MDD). The insulin independent glucose transporter 1 (GLUT1) plays a key role in brain metabolism while the insulin-dependent GLUT4 is the major glucose transporter for skeletal and cardiac muscle. We therefore examined methylation of GLUT1 and GLUT4 in fifty-two depressed inpatients and compared data to eighteen healthy comparison subjects. DNA methylation of the core promoter regions of GLUT1 and GLUT4 was assessed by bisulfite sequencing. Further factors determined were fasting glucose, cortisol, insulin, interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). We found significantly increased methylation of the GLUT1 in depressed inpatients compared to healthy comparison subjects (CG). Further findings comprise increased concentrations of fasting cortisol, glucose, insulin, and increased IL-6 and TNF-α. After six weeks of inpatient treatment, significantly lower GLUT1 methylation was observed in remitted patients compared to non-remitters. GLUT4 methylation was not different between depressed patients and CG, and did not differ between remitted and non-remitted patients. Although preliminary we conclude from our results that the acute phase of major depressive disorder is associated with increased GLUT1 methylation and mild insulin resistance. The successful treatment of depression is associated with normalization of GLUT1 methylation in remitters, indicating that this condition may be reversible. Failure of normalization of GLUT1 methylation in non-remitters may point to a possible role of impeded brain glucose metabolism in the maintenance of MDD.